2022
DOI: 10.3390/fermentation8100540
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Unsaturated Fatty Acid Ratio In Vitro on Rumen Fermentation, Methane Concentration, and Microbial Profile

Abstract: It is well known that dairy cows are fed diets with high fat content, which can adversely affect rumen fermentation. However, whether the effects of high fat content on rumen fermentation are related to the composition of fatty acids (FA) is for further study. We explored the effects of unsaturated fatty acid (UFA) ratios in vitro on rumen, methane concentration and microbial composition under the same fat levels. The experiment included a low-unsaturated group (LU, UFA proportion: 42.8%), a medium-unsaturated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Moreover, palm oil rich in saturated fatty acids is generally used as rumen bypass fat because they do not have negative effects on rumen fermentation compared with unsaturated oils [ 54 ]. In contrast, more studies in vitro and in vivo showed that dietary fatty acids could change the rumen fermentation and rumen microorganisms [ 55 , 56 ]. Studies in dairy cows and calves showed that unsaturated fatty acids (e.g., linoleic acid, linolenic acid) have adverse effects on rumen microbiota and its fermentative activity compared with saturated fatty acids (palmitic acid) [ 57 , 58 ] probably due to more toxic of dietary PUFAs to rumen microbiota than SFAs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, palm oil rich in saturated fatty acids is generally used as rumen bypass fat because they do not have negative effects on rumen fermentation compared with unsaturated oils [ 54 ]. In contrast, more studies in vitro and in vivo showed that dietary fatty acids could change the rumen fermentation and rumen microorganisms [ 55 , 56 ]. Studies in dairy cows and calves showed that unsaturated fatty acids (e.g., linoleic acid, linolenic acid) have adverse effects on rumen microbiota and its fermentative activity compared with saturated fatty acids (palmitic acid) [ 57 , 58 ] probably due to more toxic of dietary PUFAs to rumen microbiota than SFAs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, the lower volume of gas production for treatments that contain 10 and 15% French fries waste could be attributed to the negative effects of unsaturated fatty acids on rumen bacterial fermentation. Yang et al [27] using the in vitro gas production technique, showed that an increasing proportion of unsaturated fatty acids in the fermentation substrate reduces CH4 and CO2 emissions, affecting rumen fermentation and the microbial community. Also, other studies mentioned that the inhibition of unsaturated fatty acids on rumen fermentation may be due to FA adhering to the feed surface and the toxic effects of FA on rumen bacteria [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…However, compared to CT, supplementation with TSO decreased the concentration of C18:1n9c and C18:0. The inhibition effect of fatty acids on rumen fermentation may be due to fatty acids adhering to the feed surface, hindering microorganism decomposition of the feed substrate [ 59 ].…”
Section: Discussionmentioning
confidence: 99%